FTIR, CHNS and XRD analyses define mechanism of glyphosate herbicide removal by electrocoagulation - Danial, Rabiatuladawiyah; Sobri, Shafreeza; Abdullah, Luqman Chuah; Mobarekeh, Mohsen Nourouzi (Elsevier, 2019)
In this study, the performance of glyphosate removal in an electrocoagulation batch with two electrodes formed by the same metal type, consisting of aluminum, iron, steel and copper have been compared. The aim of this study intends to remove glyphosate from an aqueous solution by an electrocoagulation process using metal electrode plates, which involves electrogeneration of metal cations as coagulant agents. The production of metal cations showed an ability to bind together to form aggregates of flocs composed of a combination of glyphosate and metal oxide. Electrocoagulation using aluminum electrodes indicated a high percentage removal of glyphosate, 94.25%; followed by iron electrodes, 88.37%; steel electrodes, 62.82%; and copper electrodes, 46.69%. The treated aqueous solution was then analyzed by Fourier Transform Infrared Spectroscopy. Percentages of Carbon, Hydrogen, Nitrogen, Sulfur remaining in the treated aqueous solution after the electrocoagulation process have been determined. The treated water and sludge were characterized and the mechanism of the overall process was concluded as an outcome. An X-Ray Diffraction analysis of dried sludge confirmed that new polymeric compounds were formed during the treatment. The sludge composed of new compounds were also verified the removals. This study revealed that an electrocoagulation process using metal electrodes is reliable and efficient.